PERAN PESANTREN DALAM PERKEMBANGAN PENALARAN MORAL SANTRI: Studi Kasus Di Pesantren Tarbiyatut Tholabah Lamongan - Raikhan, Raikhan (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
Moral in the world of psychology has three domains, namely cognitive / reasoning, behavior / behavior, and affection / emotion. Moral is influenced by many elements, especially age, adolescence as an important period in which many changes in the period, both physical and non- physical, the transition period, the problem-prone period, the search for identity, and adolescence to adulthood. In the cognitive domain or moral reasoning, adolescence is crucial to the success of the self in the future. Pesantren as a sub-culture of education in Indonesia has a different educational model and has been proven to produce moral cadres.This qualitative study with a case study approach using questionnaire and FGD methods in extracting the data, and based on the moral development theory of Lawrence Kohberg. From the results of this study indicate that; First, the moral reasoning of young santri has several variants of stages or levels, this is because the santri of the pesantren also vary from the students of Tsanawiyah, aliyah, and post-student level so that the general reasoning of Tarbiyatut Tholabah Islamic boarding school students in conventional stage III is in the interpersonal agreement orientation reasoning and stage IV namely the orientation of law and order and post conventional stage V namely the orientation of legalistic social contracts. Second; religious understanding has an important role in the moral reasoning of adolescent students through two things: first, with understanding of religion, adolescents know the moral behaviors that apply, and are based on religious value standards; Second, understanding religion will generate strong motivation for adolescent students to think, and behave in accordance with religious values that are believed to be a form of worship and that can be accepted by their environment, so that from this study also found the longer children live in pesantren, then moral reasoning santri teenagers will be better. Third; The role of pesantren in the moral reasoning of young students.